Amplifying Voices: Enhancing EFL Speaking through Video-Based Assessment - Atha Ghina Zaim, Dhiya; Setyarini, Sri; Purnawarman, Pupung (International Journal of Language Teaching and Education, 2026)
Speaking is a fundamental skill in English language learning, yet many students face various challenges in developing it effectively. To address these issues, several strategies can be implemented, one of which is video-based assessment. This study investigates the impact of video-based assessment on students’ speaking performance and explores their responses to its implementation. A qualitative research design was employed, involving the use of video-based tasks and interviews with participants. The assessment procedure followed step-by-step guidelines adapted from Dal (2010), based on the Task-Based Learning framework proposed by Willis (1996). The participants were 11th-grade high school students. The results showed that nearly all students experienced improvements in their speaking scores from the first to the third video submission. An increase was also observed in the class average score. In addition, score classification using Harris’s (1974) criteria indicated a shift from lower to higher performance categories. Students expressed positive responses toward video-based assessment, citing benefits such as increased self-confidence, reduced nervousness, enhanced creativity, greater opportunities to practice English outside of class, improved speaking skills, self-reflection, and a platform to share personal interests. Despite these benefits, students also encountered some challenges, including repeated video recordings, editing difficulties, sound issues, and limited phone storage capacity.